Battling Marriage Laws: Early Marriage and Online Youth Piety in Indonesia - Nisa, Eva F. (Hawwa, 2022)
Indonesia has long faced issues relating to child marriages. This article will focus on the approaches taken by diverse parties to the issue of early marriage, including the government, civil society organisations, and young Indonesians themselves. Indonesia has witnessed the growth of online campaigns spearheaded by conservative Muslim youth promoting early marriage to prevent zina (adultery and fornication). Previously, the practice of early and child marriage was closely interconnected to rural areas, poverty, patriarchal norms, family honour, and low-level access to education. Today, early marriage does not exclusively relate to low socio-economic populations in rural areas; instead, emerging trends demonstrate that middle-class youth in urban areas professing to return to the true path of their religion are also turning to early marriage. These tech-savvy generations are aligning honour with piety in order to justify the decision to marry young, impacting on the ongoing battle against early marriage in the country.